The Massive and Quiescent Elliptical Host Galaxy of the Repeating Fast Radio Burst FRB 20240209A - T. Eftekhari; Y. Dong; W. Fong; V. Shah; S. Simha; B. C. Andersen; S. Andrew; M. Bhardwaj; T. Cassanelli; S. Chatterjee; D. A. Coulter; E. Fonseca; et al. (The Astrophysical Journal Letters)
The discovery and localization of FRB 20240209A by the Canadian Hydrogen Intensity Mapping Fast Radio Burst (CHIME/FRB) experiment marks the first repeating FRB localized with the CHIME/FRB Outriggers and adds to the small sample of repeating FRBs with associated host galaxies. Here we present Keck and Gemini observations of the host that reveal a redshift z  = 0.1384 ± 0.0004. We perform stellar population modeling to jointly fit the optical through mid-IR data of the host and infer a median stellar mass log( M _* / M _⊙ ) = 11.35 ± 0.01 and a mass-weighted stellar population age  ~11 Gyr, corresponding to the most massive and oldest FRB host discovered to date. Coupled with a star formation rate  <0.31 M _⊙ yr ^−1 , the specific star formation rate  <10 ^−11.9 yr ^−1 classifies the host as quiescent. Through surface brightness profile modeling, we determine an elliptical galaxy morphology, marking the host as the first confirmed elliptical FRB host. The discovery of a quiescent early-type host galaxy within a transient class predominantly characterized by late-type star-forming hosts is reminiscent of short-duration gamma-ray bursts, Type Ia supernovae, and ultraluminous X-ray sources. Based on these shared host demographics, coupled with a large offset as demonstrated in our companion Letter, we conclude that preferred sources for FRB 20240209A include magnetars formed through merging binary neutron stars/white dwarfs or the accretion-induced collapse of a white dwarf, or a luminous X-ray binary. Together with FRB 20200120E localized to a globular cluster in M81, our findings provide strong evidence that some fraction of FRBs may arise from a process distinct from the core collapse of massive stars.